Impacts of fires on the woody stratum of Mbam and Djerem National Park (Cameroon) - Christelle, Dadem Gueguim; Martin, Tchamba N.; T. Herman, Zanguim; Corneille, Fotso Roger (International Journal of Forest, Animal and Fisheries Research, 2020)
In Cameroon, the recurrent and uncontrolled use of bush fires, causing damage to the ecosystem, and constitutes a worrying situation for protected area managers. . The Mbam et Djerem National Park (PNMD) is threatened by bush fires and particularly by uncontrolled late fires which compromise all of its biodiversity and the future of the park. Faced with this increasingly high occurrence of fires and the insufficiency of basic data, it becomes urgent to assess the impacts of fire on the woody and grassy stratum according to the fire regime and at the end of proposing fire management strategies at PNMD level. To do this, experimental plots were installed, the impacts of fire on vegetation according to fire regimes were assessed. The results reveal that: 74% of the trees examined are barked by fire and the proportion of these barked trees varies according to the species of tree, which constitutes entry points for termites and bees in the trees. Adults are significantly more skinned (70%) than young people (30%) (variance = 32.447 df = 1, χ2 = 103.014, p = 0.004). The intensity of the fire is significantly different from one fire regime to another (p = 0.0154). The rate of regrowth is different between treatments (ANOVA, p = 0.005). High (apparent) mortality is observed for class 2 individuals (35%), i.e. juveniles suffering from late fires. Remote sensing therefore appears to be a more valuable tool for monitoring and analyzing space and time for strategic and operational planning and for early warning in the management of bush fires.